FEMINIST EXISTENTIALISM AS PORTRAYED BY THE MAIN CHARACTER IN THE MOVIE ENTITLED ENOLA HOLMES - Pramita Anindita, Ni Made; Ida Setianingsih, Ni Ketut Alit; Santi Indriani, Ketut (Udayana Journal of Social Sciences and Humanities; Vol 8 No 2 (2024): Vol 8 No 2 (2024): UJoSSH, September2024DO - 10.24843/UJoSSH.2024.v08.i02.p01, 2024)
This study entitled Feminist Existentialism as Portrayed by the Main Character in the Movie Entitled Enola Holmes. There are two aims in this study; analyze the characterization of the main character, conflicts faced by the main character, and how the conflicts faced by the main character correspond to the feminist existentialism ideologies. This study used Enola Holmes movie as a primary data and the transcript of the movie as the supporting data. This study applied documentation as a method and note taking as the technique of collecting the data. This study used a qualitative method to analyze the data and descriptively present the data by using informal method. Two theories were applied in this study. First is the theory of characterization and conflict proposed by Kenney (1966) and the second is theory of feminist existentialism proposed by Beauvoir (1949). The analysis found that there are two methods of characterization used in the movie to describe the personalities of Enola Holmes as the main character, there are dramatic method and character on the other character method. These two methods of characterization showed that Enola Holmes described as a smart and independent young woman. Based on the analysis of the conflict, it was found that the main character faced internal conflict within herself and external conflict between herself and the other characters in the movie. The conflicts she faced also correspond to the ideologies of feminist existentialism that said women have to go beyond the boundaries and limitations, and woman can become intellectuals. Key Terms: Characterization, Conflict, Feminist Existentialism